Anti-CRISPR proteins trigger a burst of CRISPR-Cas9 expression that enhances phage defense - Rachael E. Workman; Marie J. Stoltzfus; Nicholas C. Keith; Chad W. Euler; Joseph Bondy-Denomy; Joshua W. Modell (Cell Reports, 2024)
Summary: CRISPR-Cas immune systems provide bacteria with adaptive immunity against bacteriophages, but they are often transcriptionally repressed to mitigate auto-immunity. In some cases, CRISPR-Cas expression increases in response to a phage infection, but the mechanisms of induction are largely unknown, and it is unclear whether induction occurs strongly and quickly enough to benefit the bacterial host. In S. pyogenes, Cas9 is both an immune effector and auto-repressor of CRISPR-Cas expression. Here, we show that phage-encoded anti-CRISPR proteins relieve Cas9 auto-repression and trigger a rapid increase in CRISPR-Cas levels during a single phage infective cycle. As a result, fewer cells succumb to lysis, leading to a striking survival benefit after multiple rounds of infection. CRISPR-Cas induction also reduces lysogeny, thereby limiting a route for horizontal gene transfer. Altogether, we show that Cas9 is not only a CRISPR-Cas effector and repressor but also a phage sensor that can mount an anti-anti-CRISPR transcriptional response.